Psychophysiological Responses of Exercise Distribution During High Intensity Interval Training Using Whole Body Exercise - Machado, Alexandre F.; Zovico, Paulo Vinicios Camuzi; Evangelista, Alexandre L.; Rica, Roberta L.; Miranda, João Marcelo de Q.; Alberton, Cristine Lima; Bullo, Valentina; Gobbo, Stefano; Bergamin, Marco; Baker, Julien S.; Bocalini, Danilo S. (Frontiers in Physiology, 2022)
The time-efficient nature of HIIT using bodyweight exercises can facilitate the application of exercise programs at home by encouraging more people to perform regular physical exercise. However, there are no studies investigating the influence of the distribution /order of exercises during HIIT training sessions using this method. The aim of the present study was to evaluate the effects of different exercise orders on training load indicators during HIIT sessions using body weight. Twenty male participants performed three 20-min sessions of HIIT using whole body exercise, consisting of 20 sets with 30 seconds of activity performed at maximal intensity, followed by 30 seconds of passive recovery. Three designs of exercise protocols were randomly performed according to the following exercise distribution: A: jumping jack, burpee, mountain climb and squat jump); B: jumping jack, mountain climb, burpee, and squat jump) and C: burpee, squat jump, jumping jack and mountain climb. No differences were found between protocols for relative heart rate, perceived exertion, and lactate concentrations. Significant differences (p<0.001) were found for the number of movements (A:712±59, B:524±49, C:452±65). No differences were observed for the area under curve when examining perceived exertion between protocols. However, the values for perceived recovery significantly differed (p<0.001) between protocols (A:64±19; B:52±11; C:17±13). Feeling scale values were not different between protocols. Interestingly, protocol B and C induced a displeasure perception compared to protocol A. Our findings suggest that exercise distribution using HIIT whole body exercise promotes alterations in training load parameters during exercise using HIIT whole body exercises.